Selecting Principle of Floating Member of 2K-H Planetary Gear for Load Balancing Design - Cai Weixing; Tang Jinyuan (Jixie chuandong)
Taking the 2K- H planetary gear train as object,the load balancing problem caused by manufacturing and assembly errors of 2K- H planetary gear train is studied by using the analytical method. The spring series parallel mechanical model of load transfer is given,based on the geometric equivalent relationship,the relations between load balancing of planetary gears and mesh clearance,meshing stiffness are derived. The vector method is also used to deduce the calculation formula of the meshing clearance of mutually meshing tooth on the meshing line which is a result of the deviation of circle center caused by the manufacturing error and assembly error. On the basis of the meshing clearance calculation formula,the floating piece balance load is analyzed,the multivariate equations of load floating computing is obtained,to solve the equations,the following conclusion is given:（1） When the number of planet gears n < 3,the gear train partial load of the basic member can be compensated by the error of the planet wheels.（2）When the number of planet gears n≥4,the errors of the planet wheels cannot be compensated by the basic components floating,only can be compensated through the floating planetary gear. At the same time,the method of theoretical calculation of the floating amount is given. And the finite element simulation is carried out,the results and the theoretical calculation results are highly consistent.